(untitled) (Marketing Journal, 2025)
The article discusses how the importance of cash is diminishing against the backdrop of increasingly electronic payment systems in many countries, considering that the 21st century is the age of technology. Taking these changes into account, the study analyzes the potential positive outcomes for our countryʼs economy through 170 enhancing payment transparency and reducing costs by decreasing the relevance of cash in the modern economy. Additionally, proposals for implementing electronic money in our republic have been developed based on the examination of foreign experiences.